PENDIDIKAN KARAKTER BAGI ANAK USIA DINI PERSPEKTIF ISLAM - Retnaningrum, Wulandari (IAIIG Cilacap, 2018)
Economis crisis problems affect the education system. Education in Indonesia emphasizes results more than processes and further develops intelligence. Parents will feel more happy and proud if their children are smart in the field of technology and science than having children who have good character. The demand to teach children to learn to read, write and count early will result in the implementation of the teaching and learning process of early childhood education. Learning emphasizes cognitive development and this is very contrary to the characteristics of early childhood.Learning about religious knowledge, reading and writing the Al-Qur’an and reading prayers with a memorization system. This learning process will make religion a separate subject. The learning process for early childhood is more useful when emphasizing ways of habituation and example. Character education is very important to be instilled early so children can behave well. The process of coaching and character education must be planned because the character cannot be formed easily and in a short time. The application of early childhood education is inseparable from the teaching of Islam in the Al-Qur’an and Al-Hadith as the main and fundamental provisions so that children can live life in the world based on the teachings of Islam and make the child of a scientist who is pious.